Studying the ability of lactobacillus bacteria to inhibit the growth of uropathogens and their adhesion to uroepithelial cells (Journal of the College of Basic Education, 2022)
Twenty vaginal swab samples were obtained from healthy married women(with and without children),all sample were subjected to conventional morphological and cultural characteristics.12 isolates distributed among(Lactobacillus acidophilus(3),Lactobacillus casei(4)